Beneficial effects of physical exercise and an orally active mGluR2/3 antagonist pro-drug on neurogenesis and behavior in an Alzheimer's amyloidosis model - Perez Garcia, Georgina; Bicak, Mesude; Buros, Jacqueline; Haure-Mirande, Jean-Vianney; Perez, Gissel M.; Otero-Pagan, Alena; Gama Sosa, Miguel A.; De Gasperi, Rita; Sano, Mary; Gage, Fred H.; Barlow, Carrolee; Dudley, Joel T.; et al. (Frontiers in Dementia, 2023)
Background: Modulation of physical activity represents an important intervention that may delay, slow, or prevent mild cognitive impairment (MCI) or dementia due to Alzheimer's disease (AD).One mechanism proposed to underlie the beneficial effect of physical exercise (PE) involves the apparent stimulation of adult hippocampal neurogenesis (AHN). BCI-838 is a pro-drug whose active metabolite BCI-632 is a negative allosteric modulator at group II metabotropic glutamate receptors (mGluR2/3). We previously demonstrated that administration of BCI-838 to a mouse model of brain accumulation of oligomeric Ab E22Q (APP E693Q = "Dutch APP") reduced learning behavior impairment and anxiety, both of which are associated with the phenotype of Dutch APP mice.Methods: mice 3-month-old administrated with BCI-838 and physical exercise for 1 month and then tested in novel object recognition, neurogenesis, and RNAseq.Results: Here we show that (i) administration of BCI-838 and a combination of BCI-838 and PE enhanced AHN in a four-month old mouse model of AD amyloid pathology (APP KM670/671NL / PSEN1 Δexon9 = APP/PS1), (ii) administration of BCI-838 alone or with PE led to stimulation of AHN and improvement in recognition memory, (iii) the hippocampal dentate gyrus transcriptome of APP/PS1 mice following BCI-838 treatment showed up-regulation of brain-derived neurotrophic factor (BDNF), PIK3C2A of the PI3K-mTOR pathway, and metabotropic glutamate receptors, and down-regulation of EIF5A involved in modulation of mTOR activity by ketamine, and (iv) validation by qPCR of an association between increased BDNF levels and BCI-838 treatment.Conclusion: Our study points to BCI-838 as a safe and orally active compound capable of mimicking the beneficial effect of PE on AHN and recognition memory in a mouse model of AD amyloid pathology.